Biomechanical Assessment of the Anterolateral Ligament of the Knee: A Secondary Restraint in Simulated Tests of the Pivot Shift and of Anterior Stability. (1st June 2016) - Thein, Ran; Boorman-Padgett, James; Stone, Kyle; Wickiewicz, Thomas L.; Imhauser, Carl W.; Pearle, Andrew D.
Abstract : Background: Injury to the lateral capsular tissues of the knee may accompany rupture of the anterior cruciate ligament (ACL). A distinct lateral structure, the anterolateral ligament, has been identified, and reconstruction strategies for this tissue in combination with ACL reconstruction have been proposed. However, the biomechanical function of the anterolateral ligament is not well understood. Thus, this study had two research questions: (1) What is the contribution of the anterolateral ligament to knee stability in the ACL-sectioned knee? (2) Does the anterolateral ligament bear increased load in the absence of the ACL? Methods: Twelve cadaveric knees from donors who were a mean (and standard deviation) of 43 ± 15 years old at the time of death were loaded using a robotic manipulator to simulate clinical tests of the pivot shift and anterior stability. Motions were recorded with the ACL intact, with the ACL sectioned, and with both the ACL and anterolateral ligament sectioned. In situ loads borne by the ACL and anterolateral ligament in the ACL-intact knee and borne by the anterolateral ligament in the ACL-sectioned knee were determined. Results: Sectioning the anterolateral ligament in the ACL-sectioned knee led to mean increases of 2 to 3 mm in anterior tibial translation in both anterior stability and simulated pivot-shift tests. In the ACL-intact knee, the load borne by the anterolateral ligament was a mean of ⩽10.2 N in response to anterior loads and <17 N in response to the simulated pivot shift. In the ACL-sectioned knee, the load borne by the anterolateral ligament increased on average to <55% of the load normally borne by the ACL in the intact knee. However, in the ACL-sectioned knee, the anterolateral ligament engaged only after the tibia translated beyond the physiologic limits of motion of the ACL-intact knee. Conclusions: The anterolateral ligament is a secondary stabilizer compared with the ACL for the simulated Lachman, anterior drawer, and pivot shift examinations. Clinical Relevance: Since the anterolateral ligament engages only during pathologic ranges of tibial translation, there is a limited need for anatomical reconstruction of the anterolateral ligament in a well-functioning ACL-reconstructed knee.